PILKADA CALON TUNGGAL DI KABUPATEN PATI TAHUN 2017: SUATU TINJAUAN OLIGARKISME PARPOL - Achmad Ronggo Prihatmono; Kris Nugroho (Universitas Airlangga, 2020)
The phenomenon of a single candidate lately happens a lot in Indonesia, especially in the sphere of local election democratic parties. In the elections held simultaneously in Indonesia in 2017, many regions in the elections were only attended by one candidate pair. This makes the climate of competition in democracy not as expected with democracy. Democracy aims to make elite circulation happen, so that the ruling elite does not dominate so that it becomes an oligarchy. Democracy can turn into an oligarchy if a small group of groups dominates and tries to maintain power in order to remain in the circle of power. We have encountered many oligarchs in political parties, where the DPP of political parties determines the direction of political parties, even in determining the candidates to be carried by political parties in the elections and political lobbying in forming coalitions. The author uses the theory of iron oligarchy Robert Michels as an analytical aid. The research method uses descriptive qualitative research methods in explaining the phenomena that occur. Research data obtained through in-depth interviews with informants. The results show that the phenomenon of a single candidate is not always due to the high electability of a candidate pair, it can also occur because of the dominant oligarchy in political parties at the central level affects to the regional level.